Prevention of Sexual Abuse in Children with Mental Disability: A Systematic Literature Review - Farlina, Mutia (The Center for Disability Studies and Services Brawijaya University, 2019)
Children with mental retardation have a 2.5 times higher risk of child sexual abuse (CSA) than other normal children. Mentally retarded children tend to experience verbal ability barriers in describing CSA cases. This study aims to describe the prevention of CSA by parents, teachers and health professionals, including the risk of CSA in mentally retarded children, need for CSA prevention, form of CSA prevention and effectiveness of CSA prevention in mentally retarded children. Method: PRISMA was used as a guide in compiling the systematic literature review based on the inclusion criteria to determine research articles, search strategies, and research findings. Four databases used in this research included Sage Journal, Ebsco Host, Scopus and Taylor & Francis (Social Sciences & Humanities Subject). Results: mentally retarded children have a higher risk of CSA than other normal children. The need for CSA prevention are felt by parents and teachers because of the lack of knowledge and ability to do prevention. The form of CSA prevention can be done with various efforts from various parties including parents. The CSA prevention program through role-play or training to face threatening situations is effective for mentally retarded children. It is expected that these findings will become a reference for nurses in ensuring the need for CSA prevention knowledge and ability for mentally disabled children.